2020
DOI: 10.3389/fimmu.2020.605024
|View full text |Cite
|
Sign up to set email alerts
|

All About the RNA: Interferon-Stimulated Genes That Interfere With Viral RNA Processes

Abstract: Interferon (IFN) signaling induces the expression of a wide array of genes, collectively referred to as IFN-stimulated genes (ISGs) that generally function to inhibit viral replication. RNA viruses are frequently targeted by ISGs through recognition of viral replicative intermediates and molecular features associated with viral genomes, or the lack of molecular features associated with host mRNAs. The ISGs reviewed here primarily inhibit viral replication in an RNA-centric manner, working to sense, degrade, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 191 publications
(310 reference statements)
1
81
0
2
Order By: Relevance
“…Remarkably, vitamin C upregulated the expression of the viral-sensing receptors RIG-1 and MDA-5 in both humans and mice (Figure 3A-C). Furthermore, vitamin C also led to the upregulation of several other ISGs, including OAS1, 2, and 3, which sense RNA and lead to the synthesis of RNase, which can degrade viral RNA [27,40]. Furthermore, IFITMs that have been reported to be highly expressed in barrier cells such as epithelial cells were also upregulated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Remarkably, vitamin C upregulated the expression of the viral-sensing receptors RIG-1 and MDA-5 in both humans and mice (Figure 3A-C). Furthermore, vitamin C also led to the upregulation of several other ISGs, including OAS1, 2, and 3, which sense RNA and lead to the synthesis of RNase, which can degrade viral RNA [27,40]. Furthermore, IFITMs that have been reported to be highly expressed in barrier cells such as epithelial cells were also upregulated.…”
Section: Discussionmentioning
confidence: 97%
“…The xenobiotic response via the aryl hydrocarbon receptor (AHR) pathway was upregulated, and aldehyde dehydrogenase 3B (ALDH3B)-the molecule in the network-is an integral part of this pathway. Several tripartite motif proteins (TRIMs) are also upregulated in the network, and TRIM29 is reported to be involved in macrophage activation in response to respiratory infections [27].…”
Section: Transcriptomic Changes In Beas-2b Cells After Treatment With Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…HEM45: HeLa estrogen-modulated, band 45) is an RNA exonuclease that has been studied to have a broad antiviral activity. Expression of ISG20 can be regulated by both type I and II interferons (IFNs) and it plays a role in mediating interferon’s antiviral activities 25 , 45 , 46 . Pentecost group, showed that ISG20 mediates estrogen controlled cellular proliferation and differentiation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The main effector functions of ISGs are to target pathways and functions required during the pathogens’ life cycle as well as to enhance innate immune signaling. In addition, ISGs encode proapoptotic proteins that lead cells to apoptosis under specific conditions [ 32 , 33 ].…”
Section: Recognition and Reaction Of Immune Cells To Nucleic Acidsmentioning
confidence: 99%